Analisis Performa website Unipem menggunakan GTMetrix dan Google PageSpeed Insight - Muhammad Arif Kurniawan; Samsul makin (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2023)
The development of Information Technology (IT) has had a positive impact, especially in the context of businesses. One of the outcomes of IT development that has facilitated information dissemination is websites. websites play a crucial role in educational institutions for information dissemination and communication. Therefore, the quality of website services becomes a top priority in improving the quality of information delivery services in universities. This research aims to evaluate the performance of the Universitas Insan Pembangunan website, focusing on two pages: unipem.ac.id and pmb.unipem.ac.id. performance testing was conducted using the web applications GTMetrix and Google PageSpeed Insight. The testing results provide information about page loading speed, performance scores, and issues affecting website performance. The results show that the pmb.unipem.ac.id page performs better than the unipem.ac.id page. The pmb.unipem.ac.id page achieved a grade B score with a performance score of 80% and Structure score of 81%, while the unipem.ac.id page received a grade C score with a performance score of 79% and Structure score of 65%. Testing with Google PageSpeed Insight also yielded higher performance scores for the pmb.unipem.ac.id page. Several issues were identified during the testing, including large file sizes, render-blocking resources, and the need for Content Delivery Network (CDN) usage. Recommendations for improvements were provided based on the testing results to enhance website performance, such as avoiding large network payloads, optimizing image sizes, using efficient cache policies, eliminating render-blocking resources, and considering CDN usage.